President's Message - Khotar, Rupinder (Operating Room Nurses Association of Canada Journal, 2014)
I am fortunate to know many learned individuals. I have been mentored, coached and taught by some exemplary people. They have influenced my professional and personal life over the years. I recently approached a few of them to help me work through a major professional decision and they stepped forward, when asked, and never denied me the attention that I sought. Each person contributed valuable insights and shared life experiences that helped to shape my decisionmaking process. I experienced deep gratitude and humility in their presence.